‘Believing na evill nor injury’: Space, Place, and Crime in Sixteenth-Century Scottish Burghs - Falconer, Robert (My University, 2025)
On 1 August 1582, around ‘five hours efter noone’, Margaret Cryst, Jonet Porteous, and Elizabeth Crawford violently assaulted Margaret Leggat in ‘hir own dwelling hous’ in Canongate. After entering Leggat’s home, the trio ‘cast her downe upoun the floore’, punched and kicked her ‘in the wambe’, grabbed her by the arms, pulled off her curche (cap), and proceeded to strike her repeatedly with a set of iron tongs. Afterward, the group departed the house, taking with them the iron tongs and a piece of linen broadcloth. At first glance, the account suggests that this was a simple case of theft with violence. However, the entire encounter needs to be set within a broader, ongoing dispute. The court records go on to state that after leaving the house, Cryst ‘came at the samyn tyme upoun’ Alison Leggat and her husband, Robert Bond. She began to verbally assault the couple, calling Alison a ‘comon theif, biche huir, and the said Robert a comoun theif’. Cryst added that ‘the said Alesoun wold do with the said robert as she did with hir first guid man and that all the bairnis quhilkis she buir was neuer ane of thame his bot uther mens’. But this was not the end of Cryst’s attack on the Leggat family. Later that evening, Cryst went to ‘the duelling house of Duncan Garlaw’ where Alison and Robert were at their supper ‘in maist quiet manner’. In front of Garlaw, Cryst repeated the ‘former iniurious wordis’.
Keywords: Scottish Burghs; crime; sixteenth-century